Registration of 'Saluki 4313' Soybean with High Yield and High Resistance to SCN HG Type 0 (Race 3). Issue 1 (22nd September 2014) - Kantartzi, Stella K.
Abstract : 'Saluki 4313' soybean [ Glycine max (L.) Merr.] (Reg. No. CV‐515, PI 672534) was developed by the Southern Illinois Breeding and Genetics Program and released in May 2013. The objective was the development of a non‐genetically modified cultivar with high yield, high resistance to soybean cyst nematode ( Heterodera glycines Ichinohe) (SCN) HG Type 0 (Race 3), and good adaptation to the midwestern United States. Saluki 4313 is an F5 –derived line produced from the cross SS98‐7851 × 'LD00‐3309' using the single‐pod descent breeding method. Saluki 4313 was tested for its yield performance in 2011 and 2012 in the USDA Uniform MGIV Tests, Northern States and the SCN Regional Uniform MGIV Tests and ranked first and second, respectively, compared with other breeding lines and checks. Saluki 4313 showed high resistance to SCN HG Type 0 (Race 3) in the USDA Uniform MGIV Tests, Northern States and the SCN Regional Uniform MGIV Tests. Saluki 4313 was released because it combines high yield with high resistance to SCN HG Type 0 (Race 3). Saluki 4313 was released in the spring of 2013 because of its competitive yield and high resistance to SCN HG Type 0 (Race 3) for conventional farming systems in the U.S. Midwest, in countries where genetically modified crops are not allowed, and as an elite parent for breeding programs.